Henrik Pontoppidans dobbeltportræt af Skagen - Nordby, Thomas (Pontoppidaniana, 2025)
Abstract Henrik Pontoppidan’s story En Fiskerrede from the autumn of 1883 which takes place at The Skaw both some time in the past and in the present, is written up against Holger Drachmann’s successful musical play Strandby Folk, which premiered at Det kongelige Teater (The Royal Theatre) in the spring of 1883. Where Drachmann gives a glorified depiction of the heroic rescue efforts provided by the fishermen of the Skaw, Pontoppidan portrays the fishermen and the sailors as executioners and victims respectively both in the past and in the present. Civilisation is only a thin layer of varnish over the same cruel greed as before. The criticism of the exploitation of the stranded sailors carried out by the fishing community and of the distanced hunger for adventure on the part of the artists draws a pessimistic picture of civilisation – and of human nature which seems valid at all times. The text – supported by the symbolic language – enrolls with its determinism in naturalism with its description of ‘la bête humaine’.